Analisis Pengaruh Work Stress and Burnout Terhadap Kinerja Karyawan di DKI Jakarta Selama Pandemi COVID-19 - Mohammad Ichsan; Agung Sudjatmoko; Shifa Aprilianti; Amanda Putri Nurshavira (Jurnal Ecogen, 2022)
Abstract: This research was created with the aim to find out how the effects of Work Stress, and Burnout on Employee Performance in DKI Jakarta during the COVID-19 Pandemic. Based on the results of this study is expected to provide input, both to the company and to the employees themselves. This aims to find the most effective way so that employees can work comfortably and can still produce a good performance and still maintain the quality of the company. The data collection method used questionnaires to 200 people as respondents. Data analysis techniques use multiple linear regression analysis. Therefore, if Work Stress and Burnout can be controlled then employees are able to provide their best performance for the company as well as for the community